Tobacco Hornworm Manduca sexta (Linnaeus) (Insecta: Lepidoptera: Sphingidae) - Morgan A. Byron; Jennifer L. Gillett-Kaufman (EDIS)
The tobacco hornworm, Manduca sexta (L.), is a common pest of plants in the family Solanaceae, which includes tobacco, tomato, pepper, eggplant, and various ornamentals and weeds (del Campo and Renwick 1999). Caterpillars in the family Sphingidae are known as hornworms, due to their worm-like body shape and the presence of a small, pointed “horn” at their posterior (Figure 1). The adult stage of Manduca sexta is a heavy-bodied moth that resembles a hummingbird, and Manduca adults are commonly referred to as hawkmoths or hummingbird moths (Figure 2). The larval stage (hornworm) of this species is more often encountered, as it is resides on the host plant during the day and can cause significant defoliation of economically important crops. [...]